2017
DOI: 10.1021/acs.jcim.6b00465
|View full text |Cite
|
Sign up to set email alerts
|

Phantom PAINS: Problems with the Utility of Alerts for Pan-Assay INterference CompoundS

Abstract: The use of substructural alerts to identify Pan-Assay INterference compoundS (PAINS) has become a common component of the triage process in biological screening campaigns. These alerts, however, were originally derived from a proprietary library tested in just six assays measuring protein–protein interaction (PPI) inhibition using the AlphaScreen detection technology only; moreover, 68% (328 out of the 480 alerts) were derived from four or fewer compounds. In an effort to assess the reliability of these alerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
224
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(238 citation statements)
references
References 31 publications
10
224
0
4
Order By: Relevance
“…[27] However,e ven for AlphaScreen, the accuracy is quite low when the filters are applied to our data. As imilar observation was made in as tudy by Capuzzi et al [11] One hypothesis may be that the relativelyl ow accuracy is due to differences between our dataset and the one on which the filters were built, in terms of compound structures as well as screening conditions, such as compound concentration. These hypotheses could not be verified as the PAINS dataset was never publicly disclosed.I ti sa lso possible that specific PAINS substructures were classified as undesirable internally and were thus not part of the screening deck.…”
Section: Application Of Pains Filterssupporting
confidence: 79%
See 1 more Smart Citation
“…[27] However,e ven for AlphaScreen, the accuracy is quite low when the filters are applied to our data. As imilar observation was made in as tudy by Capuzzi et al [11] One hypothesis may be that the relativelyl ow accuracy is due to differences between our dataset and the one on which the filters were built, in terms of compound structures as well as screening conditions, such as compound concentration. These hypotheses could not be verified as the PAINS dataset was never publicly disclosed.I ti sa lso possible that specific PAINS substructures were classified as undesirable internally and were thus not part of the screening deck.…”
Section: Application Of Pains Filterssupporting
confidence: 79%
“…Over the years, the applicability of PAINS filtersh as been discussed and criticized. [5,10,11] It has been reported that the presence of PAINS substructure does not necessarily imply an undesirable mechanism and the applicability domain of the PAINS is limited by the chemical space and the unique assay technologyu sed in buildingt he filters.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that by identifying inhibitors containing PAINs, we are not automatically claiming these compounds have been incorrectly identified as inhibitors of the GTPases or their regulators. It is important not to “black box” compounds that contain PAINs and immediately ignore them for future studies; there are FDA improved drugs that contain PAINs motifs and examples of PAINs compounds have been shown crystallographically to bind their putative targets . Indeed, some of the PAINs compounds listed in this review have persuasive in vitro and in vivo data that correlates with the inhibition of stated targets.…”
Section: Discussionmentioning
confidence: 99%
“…Es ist wichtig zu beachten, dass wir bei der Identifizierung von PAINs enthaltenden Inhibitoren nicht automatisch behaupten, dass diese Verbindungen inkorrekterweise als Inhibitoren der GTPasen oder ihrer Regulatoren identifiziert wurden. Es ist wichtig, PAINs enthaltende Verbindungen nicht sofort für zukünftige Studien zu ignorieren; es gibt von der FDA zugelassene Wirkstoffe, die PAINs‐Motive enthalten und Beispiele von PAINs‐Verbindungen, für die kristallographisch gezeigt wurde, dass sie an ihre vermeintlichen Zielstrukturen binden . In der Tat zeigen einige der in diesem Aufsatz beschriebenen Verbindungen überzeugende In‐vitro‐ und In‐vivo‐Daten, die mit der Inhibition der angegebenen Zielstrukturen korrelieren.…”
Section: Zusammenfassung Und Ausblickunclassified